The experiment on techniques used in interactive art - Lau, Leh Na. (Universiti Malaysia Sarawak (UNIMAS), 2015)
This research would discuss the experiment on the techniques that are used in interactive art. Interactive art involves the audience as a factor that influence the changes of the artwork. The artwork titled ‘Self-Confidence’ is the result of studies which discuss the techniques used in the interactive art and implies it in the artwork. The visual image encourages the involved audiences to build up their self-confidence by facing themselves. The inspiration comes from experiece of the researcher, who used to be weak in self-confidence but now getting stronger.Experiment on the techniques of frame differencing, background subtraction, and brightness thresholding that can detect the presence of an audience. To conclude the analysis, the researcher compared research of the techniques that is most suitable to apply in the interactive artwork.